2022
DOI: 10.3390/microorganisms10050884
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inhibition of Quorum Sensing as an Alternative for the Control of E. coli and Salmonella

Abstract: Quorum sensing (QS) is a process of cell–cell communication for bacteria such as E. coli and Salmonella that cause foodborne diseases, with the production, release, and detection of autoinducer (AI) molecules that participate in the regulation of virulence genes. All of these proteins are useful in coordinating collective behavior, the expression of virulence factors, and the pathogenicity of Gram-negative bacteria. In this work, we review the natural or synthetic inhibitor molecules of QS that inactivate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…Moreover, it has been reported that AI molecules participate in the regulation of virulence genes and the pathogenicity of gram-negative bacteria. [31] Similarly, the mutant strain presented a lower virulence than the wild-type strain in the G. mellonella infection model, which may be attributed to the high RNA editing level of badR, consistent with the virulence difference between QD110 and R16. Here, we draw a brief illustration to describe the roles of RNA editing on badR in K. pneumoniae (Figure S7, Supporting Information).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, it has been reported that AI molecules participate in the regulation of virulence genes and the pathogenicity of gram-negative bacteria. [31] Similarly, the mutant strain presented a lower virulence than the wild-type strain in the G. mellonella infection model, which may be attributed to the high RNA editing level of badR, consistent with the virulence difference between QD110 and R16. Here, we draw a brief illustration to describe the roles of RNA editing on badR in K. pneumoniae (Figure S7, Supporting Information).…”
Section: Discussionsupporting
confidence: 56%
“…According to earlier studies, luxS stimulates the creation of the AI-2, which may help bacteria build biofilms more effectively. 58 In this work, the presence of BAI reduced AI-2 activity and luxS expression. It suggested that BAI might act as the S. aureus LuxS/AI-2 system’s QS inhibitor.…”
Section: Resultsmentioning
confidence: 49%
“…Quorum sensing (QS) is a cell-to-cell communication system depending on small signaling molecules which are called autoinducers (AIs) [ 45 ]. The anti-virulence strategy suggested includes the disturbance of QS through different methods, such as the intervention of AI-2 synthesis and inhibition of protein in the QS system [ 46 ]. Moreover, the recent study focus on the strategy of combining QS inhibitors with antibiotics, which is a promising strategy for inhibiting the production of AI-2 and QS activity, while antibiotics have increased the resistance of pathogens [ 47 ].…”
Section: Discussionmentioning
confidence: 99%